Respuesta :
Answer:
x=-5, x=-1
Step-by-step explanation:
looking at the graph
x= -5,
x=-1
![Ver imagen wegnerkolmp2741o](https://us-static.z-dn.net/files/df4/74ff9eb3c2eb449225919bd3f507035f.png)
Answer:
At x=-5 and x=-1 f(x)=g(x)
Step-by-step explanation:
We have given that :[tex]f(x) = -2x -6[/tex]
[tex]g(x) = x^2 + 4x -1[/tex]
To determine : where f(x) = g(x)
Solution : We refer the attached graph which clearly shows that f(x) and g(x) intersect at pt (-5,4) and (-1,-4)
which implies at x= -5 and x=-4 f(x)= g(x)
or At x= -5
[tex]f(x)=-2x-6=-2(-5)-6=4[/tex]
[tex]g(x)=x^2+4x -1= (-5)^2+4(-5)-1=4[/tex]
or At x= -1
[tex]f(x)=-2x-6=-2(-1)-6=-4[/tex]
[tex]g(x)=x^2+4x -1= (-1)^2+4(-1)-1=-4[/tex]
Therefore, at x=-5 and x=-1 f(x)=g(x)
![Ver imagen DodieZollner](https://us-static.z-dn.net/files/d58/4365c85cd266b8d8d4c202a839db6625.png)